Equity Risk Premium and Regional Integration - Mohamed El Hedi Arouri; Frédéric Teulon; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2013)
This article contributes to the literature on stock market integration by developing and estimating a capital asset pricing model with segmentation effects in order to assess stock market segmentation and its effects on risk premia at the regional level. We show that the estimated degrees of segmentation vary from one region to anther and over time. Moreover, we establish that compared to developed market regions, emerging market regions have four main dissimilarities: the total risk premiums are significantly higher, more volatile, dominated by regional residual risk factors and reflect mostly regional events. However, in the recent period emerging market regions have become less segmented as a result of liberalization and reforms and the relative magnitude of the premium associated with global factors has increased.
Keywords: G15; F36; C32; 330; asset pricing; regional integration; equity risk premium